2011
DOI: 10.1159/000328667
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Pancreatic Tumors Are Risk Factors for Pancreatic Fistula after Pancreatic Surgery

Abstract: Background: Postoperative pancreatic fistula (PF) is still regarded as a major complication in pancreatic surgery. In the present study, we evaluated the risk of PF in a large study population of patients with neuroendocrine pancreatic tumors (NPT), pancreatic cancer (PC), and chronic pancreatitis (CP). Methods: Patients who underwent pancreatic surgery between 1989 and 2008 at our institution were retrospectively evaluated. Patients were analyzed regarding age, gender, BMI, alcohol, smoking, preoperative diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
2
24
3
Order By: Relevance
“…Pancreatic lesions that usually do not cause fibrotic reactions, such as PNET are generally not associated with pancreatic duct obstruction. High fistula rates after resections for PNET have been described accordingly …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic lesions that usually do not cause fibrotic reactions, such as PNET are generally not associated with pancreatic duct obstruction. High fistula rates after resections for PNET have been described accordingly …”
Section: Discussionmentioning
confidence: 99%
“…Underlying pathology is also correlated with the incidence of POPF as adenocarcinoma and chronic pancreatitis are typically associated with firm, fibrotic and thereby easily sutured glands, whereas other peri‐ampullary cancers and benign processes are associated with a soft gland . PNET rarely cause duct dilatation and fibrosis, and could therefore be associated with increased rates of POPF …”
Section: Introductionmentioning
confidence: 99%
“…High-volume pancreatic resection is a crucial criterion for having an acceptable risk of postoperative complications and surgeryrelated deaths [90] . Additionally, it should be pointed out that pancreatic surgery for PanNETs is associated with a higher risk compared with other pancreatic malignancies [91,92] . Patients with PanNETs usually have potential risk factors for pancreatic fistula such as a soft pancreatic texture and a non-dilated main pancreatic duct.…”
Section: What Is the Minimal Acceptable Rate Of Postoperative Complicmentioning
confidence: 99%
“…Rates of postoperative complications are classified according to the type of pancreatic resection. For standardized pancreatic resection, the rate of postoperative complications is around 30-50% with a mortality risk for pancreaticoduodenectomy and distal pancreatectomy of less than 5% and less than 1%, respectively [91,[93][94][95] .…”
Section: What Is the Minimal Acceptable Rate Of Postoperative Complicmentioning
confidence: 99%
“…There occurred two type A and one type B fistula, which all three resolved without any radiological intervention or reoperation. A soft consistency of the pancreatic remnant in ampullary, duodenal, and especially neuroendocrine diseases provide a significantly higher risk of pancreatic fistula [24, 25]. Several groups showed that the rate of pancreatic fistula in high-risk patients with a small fragile soft pancreatic remnant and a non-dilatated pancreatic duct was as high as 36% compared to only 2–4% in low-risk patients with a fibrotic pancreatic remnant composed of dense tissue [2629].…”
Section: Discussionmentioning
confidence: 99%